2017
DOI: 10.1186/s12957-017-1159-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and diagnostic performance of dual-tracer-guided sentinel lymph node biopsy in cT1-2N0M0 gastric cancer: a systematic review and meta-analysis of diagnostic studies

Abstract: BackgroundDual-tracer-guided sentinel lymph node (SLN) biopsy may provide a promising diagnostic tool to assess accurately the status of lymph node metastasis in the surgical operation and assure the oncologic safety of the function or stomach preserving surgery. The diagnostic performance of this technology in recent studies varied. Thus, we conducted this meta-analysis.MethodsThis systematic review and meta-analysis was registered at the PROSPERO. Eligible studies were searched in the PubMed, EMBASE, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
(36 reference statements)
1
13
0
2
Order By: Relevance
“…Therefore, we would like to focus on the mean number of SLN and to estimate its effect on the parameter of sensitivity. In the subgroup analysis, a result consistent with the previous meta‐analysis was obtained, that sensitivity was found to be significantly related to the harvested SLNs number . In addition, two IREE studies reported recalculated sensitivities by the number of lymph nodes with harvested mean SLN ≥ 5 (1.00 and 1.00, respectively) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, we would like to focus on the mean number of SLN and to estimate its effect on the parameter of sensitivity. In the subgroup analysis, a result consistent with the previous meta‐analysis was obtained, that sensitivity was found to be significantly related to the harvested SLNs number . In addition, two IREE studies reported recalculated sensitivities by the number of lymph nodes with harvested mean SLN ≥ 5 (1.00 and 1.00, respectively) .…”
Section: Discussionsupporting
confidence: 84%
“…In the subgroup analysis, a result consistent with the previous meta-analysis was obtained, that sensitivity was found to be significantly related to the harvested SLNs number. 81,82 In addition, two IREE studies reported recalculated sensitivities by the number of lymph nodes with harvested mean SLN ≥ 5 (1.00 and 1.00, respectively). 51,55 These results indirectly reflect the complicated lymphatic system of the stomach that many directions of tracer flow lead to multiple SLNs, 34 An inverse correlation was commonly reported between cT stage and SLN staging, indicating that the diagnostic accuracy decreases from cT1 to cT3 tumors.…”
Section: Meta-logistic and Subgroup Analysismentioning
confidence: 99%
“…Gastric Cancer -An Update gastric cancer. On the other hand, some researchers reported the utility of sentinel node biopsy in patients with gastric cancer [34][35][36]. Although gastric lymphatic drainage is often complicated, by using the dual tracer method with radiolabeled tin colloid and blue dye, Kitagawa reported that the sentinel node detection rate was 97.5% (387 of 397) and the accuracy of nodal evaluation for metastasis was 99% (383 of 387) in cT1 and tumors <4 cm [36].…”
Section: Lecs Plus Biopsy To Sentinel Lymph Node For Early Gastric Camentioning
confidence: 99%
“…Sentinel lymph node (SLN) biopsy, an invasive method, was used for detection of metastatic LNs in GC [9]. Studies have shown that SLN biopsy was a promising tool to assess the LN metastases in T1-2 GC patients [10][11][12]. However, there are still debates regarding the effectiveness of LN detection techniques and oncological safety of biopsy.…”
Section: Introductionmentioning
confidence: 99%